UPAYA PENANGGULANGAN MASALAH KEMISKINAN MELALUI PERENCANAAN PEMBANGUNAN BERBASIS PERTANIAN TANANAM PANGAN DI KABUPATEN WONOSOBO - Heri Cahyono, Moch Arifien (Forum Ilmu Sosial, 2016)
Food crops is one asset that can be used to address the problem of poverty. For that we need proper planning for development-oriented poverty problem can be managed properly. Planning is essentially be based on issues, basic needs and potential of the region so that development undertaken appropriate and targeted so as to boost the regional economy development of the agricultural sector related food crops sub-sector. The big difference, both physically natural or artificial between regions within a region causes the difference in opportunities to grow and develop. The main objective of this research is to make planning in the development of the agricultural sector in particular sub sectors of food crops in order to improve the regional economy by looking at the performance (performance) the agricultural sector, identifying food crops that are potential to be developed, draw up a hierarchy of centers of social services and economy, and planning the development of the agricultural sector of food crops sub sector. From the research, it was determined that the area will become a center for the production of rice, maize, cassava, sweet potatoes, beans, vegetables, and fruits. Food crops that can be developed in each sub-district is excellent commodities and the potential that crops have kompetetif and comparative advantages or one of them. Food crops that can be developed in each sub- district in Wonosobo regency are: rice, maize, cassava, sweet potatoes, beans, vegetables and fruits. Featured food crops when the mapping will be seen that there has been a regional grouping as a cluster. Of the commodity will be directed cluster development, namely the construction of production centers and processing centers.